Up close and personal: an investigation of headteacher departure from Anglican primary schools in England - Whiteoak, Daphne A. (2014)
Headteacher supply is of critical concern to policy makers and Governing Bodies in England as many schools continue to experience difficulties in recruiting school leaders despite succession planning and school organisation strategies at national and local level. Church of England schools appear to experience greater difficulties in recruitment and a lack of focus on leaders of Anglican schools in the empirical literature has resulted in little being known about the nature of Anglican school headship and why headteachers of this category of schools leave.